Ultrathin Hydrogen Diffusion Cloak. Issue 1 (1st December 2017) - Li, Yang; Liu, Chuanbao; Bai, Yang; Qiao, Lijie; Zhou, Ji
Abstract: For years, hydrogen damage is a fatal threat to metals and alloys in long‐term service. This paper introduces the transformation optics theory in metamaterials to the diffusive field, and the design of an ultrathin hydrogen diffusion cloak. Thanks to the alternately and gradually changed diffusion coefficients in adjacent layers, the laminated cloak efficiently conducts the diffusive flow to shield the central region, and drastically reduces the diffusion flux in it. More importantly, the diffusion coefficients are designed following the Laplace equation instead of conventional linear transformation, hence the cloak has a very small thickness whose core/shell ratio is two magnitudes larger than traditional designs, but the diffusion flux is even one magnitude lower. The ultrathin hydrogen diffusion cloak with excellent performance provides a promising route for hydrogen protection. Abstract : A new design of invisibility cloak adopting a new nonlinear transformation as well as a new approximation strategy is applied in hydrogen damage protection. The ultrathin thickness of the cloak and the feasibility of laminated structure with equal thickness cast light on practical applications. This design provides a universal method to be readily expended to other parabolic guided fields.